Análise da demanda por transporte ferroviário na microrregião de Toledo Paraná - Matos, Jean Carlos de (2016)
This research analyzed the demand for rail transport in the micro-region of Toledo / PR. The aim was to collect and analyze the products listed by the National Land Transportation Agency (ANTT) that were more favorable to rail transport, considering the relations of quantity transported, distance covered and sensitivity to the value of the freight. According to ANTT, the products with these features are: steel products, grain, iron ore, cement, fertilizers, oil derivatives, lime and limestone, coal, clinker and containers. It was presented the economic panorama of the micro-region of Toledo, its cargo handling dynamics relating to the products moved and features that fit the railways. Primary data were collected through the unstructured interview technique and observation. It was also used documentary research for secondary data collection in order to describe the economic scenario of the micro-region of Toledo/PR, and to understand how the movement of cargo currently happens. It was found that there is demand for rail transport in several moved products, given the context of growth and development that is presented in the micro-region, and the lack of investment in this kind of transport for both production flow as well as for the arrival of products that dynamise its economy may curb development in the medium, long term.